Efektivitas Modul Pembelajaran Tafsir Tarbawi Berbasis Model Team Based Project - Harahap, Musaddad; Sari Siregar, Lina Maya; Yunita, Yenni; Permata Sari, Diana Irma (UIR Press, 2024)
Tafsir tarbawi is a course that contains Al-Qur'anic messages about education. When viewed from the current facts, the messages of tafsir tarbawi often do not receive serious attention among students. Such an attitude does not reflect the character of prospective Muslim educators. This study examines the effectiveness of tafsir tarbawi module based on team-based project model in Islamic Education Study Program, Riau Islamic University. The purpose of the study was to develop a learning module of tafsir tarbawi based on the team-based project model. The method used is research anddevelopment with the type of Analysis, Design, Development, Implementation, Evaluations (ADDIE). Data sources were obtained from questionnaires, expert advice, and tests. Data analysis used percentage and experimental design type one grouppretest/posttest. The results showed that the tarbawi tafsir message developed in the team-based project-based learning module was very effective in improving student learning outcomes. This is based on the results of the paired samples t-Test, namely there is a mean pretest value of 39.60 and a mean posttest value of 88.67. The score interval between 39.60 and 88.67 is 49.07. This means that there is a significant difference between the pretest and posttest scores. Then from the results of the paired samples t-Test test as well, it was found that the sig. (2-tailed) of 0.000 <0.05. In conclusion, there is an increase in student learning outcomes after using the team-based project-based tarbawi tafsir learning module.